Pengaruh Model Diskursus Multi Representasi Berbantuan Cabri 3d terhadap Hasil Belajar Siswa - Riyadi, Slamet; Susilaningtyas, Tri; Mahmudah, Muhlisatul (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2020)
This study aims to: (1) Determine the effect of the Multi Representation Discourse model with 3D cabri-assisted learning outcomes of Al Kawtsar-Panti MTs students (2) Describe the Effect of the Multi Representation Discourse model with 3d cabri-assisted learning outcomes of Al Kawtsar-Panti MTs students. The research subjects were 18 students of Al Kawtsar MTs class VIIIA and 17 students of VIIIB. This research is classified as Experimental Research which compares two learning models. Based on the results of the calculation of the T Test (Independent Samples T Test) it can be seen that tcount > t table or p-value 0.03 < 0.05 then Ha is accepted and H0 is rejected, so there is an influence on the use of Multi Representation Discourse learning models assisted by 3D Cabri against student learning outcomes in the material building flat side cubes and beams class VIII at MTs Al Kawtsar - Panti.